The effect of cell cluster size on intracellular nanoparticle-mediated hyperthermia: is it possible to treat microscopic tumors?. (January 2013) - Hedayati, Mohammad; Thomas, Owen; Abubaker-Sharif, Budri; Zhou, Haoming; Cornejo, Christine; Zhang, Yonggang; Wabler, Michele; Mihalic, Jana; Gruettner, Cordula; Westphal, Fritz; Geyh, Alison; Deweese, Theodore l; et al.
Aim: To compare the measured surface temperature of variable size ensembles of cells heated by intracellular magnetic fluid hyperthermia with heat diffusion model predictions.Materials & methods: Starch-coated Bionized NanoFerrite (Micromod Partikeltechnologie GmbH, Rostock, Germany) iron oxide magnetic nanoparticles were loaded into cultured DU145 prostate cancer cells. Cell pellets of variable size were treated with alternating magnetic fields. The surface temperature of the pellets was measured in situ and the associated cytotoxicity was determined by clonogenic survival assay.Results & conclusion: For a given intracellular nanoparticle concentration, a critical minimum number of cells was required for cytotoxic hyperthermia. Above this threshold, cytotoxicity increased with increasing cell number. The measured surface temperatures were consistent with those predicted by a heat diffusion model that ignores intercellular thermal barriers. These results suggest a minimum tumor volume threshold of approximately 1 mm 3, below which nanoparticle-mediated heating is unlikely to be effective as the sole cytotoxic agent. Original submitted 31 October 2011; Revised submitted 29 February 2012; Published online 22 November 2012